Santander and its Dynamic Capabilities - Cooper, Elizabeth (2010)
The purpose of this assignment was to examine the growth of Spanish bank Santander from the strategic perspective of dynamic capabilities. By analysing the content of annual reports, as well as contemporary media accounts and individual interviews with employees, the core competencies and capabilities of the bank have been identified. From this, it has been possible to assess whether such capabilities can be considered as dynamic. This case study has found that there is a very close correlation between the theory of dynamic capabilities and how Santander has been able to grow so dramatically.